Synthesis and comparative spectroscopic studies, HOMO-LUMO analysis and molecular docking studies of 3,3′-(1,4-phenylene)bis[2-(6-chloropyridin-3-yl)prop-2-enenitrile] based on DFT - Goreci, C. Yorur (ELSEVIER, 2022)
A novel organic molecule, named as 3,3'-(1,4-phenylene)bis[2-(6-chloropyridin-3-yl)prop-2-enenitrile] (Pyr-CN)(2)B), having two pyridyl rings and cyano groups was designed and synthesize(d). Molecular structure, vibrational wavenumbers, electronic and Molecular Electrostatic Potential (MEP) properties of (Pyr-CN)(2)B molecule were investigated theoretically using Density Functional Theory (DFT). Experimental and theoretical results obtained from FT-IR, Raman and UV-Vis studies were compared to better explain the properties of the molecule. Chemical reactivity and high electron density due to the heteroatoms in its molecule structure, (Pyr-CN)(2)B molecule can be proposed as a candidate for many applications based on its chemical and electronic properties. In this scope, the effect of this functional molecule against coronavirus had been investigated by molecular docking studies. These studies had been performed to determine the interactions of the title molecule with the target macromolecule SARS-CoV-2 main protease (M-pro) inhibitor (PDB ID: 7C7P) where minimum binding energy was calculated as -7.30 kcal/mol. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Acrylonitrile; Computational studies; DFT; Molecular docking; NBO ANALYSIS; FT-IR; VIBRATIONAL-SPECTRA; RAMAN; Chemistry